Identification of preferential groundwater run-off belts through correlation between spring discharge and precipitation in Baiquan spring basin. Issue 2 (July 2021) - Yu, Yafei; Shu, Longcang; Dong, Yanan; Wang, Xin
Abstract: Baiquan spring group is a typical sign of the existence of preferential groundwater run-off belts in Baiquan spring basin. The spring flow is mainly affected by the supply of karst water, and atmospheric precipitation is the most important factor affecting the supply of karst water. By using Pearson correlation coefficient method, the number of months with the maximum Pearson coefficient between the spring discharge and the precipitation at the monthly scale of each hydrological station in the water spring area is analyzed, which is called the best precipitation delay. According to the optimal precipitation lag time, the Pearson correlation coefficients of spring discharge and precipitation of each hydrological station in 2006-2013 are calculated on the three months scale and the daily scale respectively, and the hydrological stations closely related to spring discharge are found out. The results show that: the best precipitation lag time of each station is 6 months; the precipitation change of Wangsheren station, Suncun station and Wenzu station is consistent with the spring flow process, which has a relatively large impact on the spring flow. The 3 stations may be located in the preferential groundwater run-off belts bearing medium in Baiquan spring basin.